Spatial Analysis of Prevalence of Early Marriage and HDI in Indonesia (Jurnal Matematika, Statistika dan Komputasi, 2021)
Early marriage has become an important issue in Indonesia. Even though the rate of early marriage shows a decline until 2020, the number still makes Indonesia become the country with the second highest early marriage in Southeast Asia. Early marriage that occurs can hinder the achievement of the Sustainable Development Goals (SDG) and can have an impact on the Human Development Index. The existence of a relationship between early marriage and HDI encourages researchers to conduct studies that aimed at examining the effect of the prevalence of early marriage on HDI in each district/city in Indonesia on 2020. This study uses the Geographically Weighted Logistic Regression (GWLR) analysis method with the data sourced from the National Socio-Economic Survey (SUSENAS) raw data in March 2020 and publication data on the website of The Central Bureau of Statistics. The results of the analysis found that the prevalence of early marriage has a negative and significant effect in several districts/cities in the Provinces of Aceh, North Sumatra, West Sumatra, Riau, Jambi, South Sumatra, Bengkulu, Lampung, Bangka Belitung Islands, Riau Islands, West Java, Central Sulawesi, South Sulawesi, Southeast Sulawesi, Maluku, and West Papua. This research is expected to be a recommendation for the government and community organizations to conduct socialization regarding the maturity age of marriage and the adverse effects that can be caused by early marriage.
Keywords: Early Marriage; Human Development Index; Geographically Weighted Logistic Regression